Appropriate Separator Sizing: A Modified Stewart and Arnold Method. (29th November 2012) - Boukadi, F.; Singh, V.; Trabelsi, R.; Sebring, F.; Allen, D.; Pai, V.
Abstract : Oil and gas separators were one of the first pieces of production equipment to be used in the petroleum industry. The different stages of separation are completed using the following three principles: gravity, centrifugal force, and impingement. The sizes of the oil droplets, in the production water, are based mainly on the choke valve pressure drop. The choke valve pressure drop creates a shearing effect; this reduces the ability of the droplets to combine. One of the goals of oil separation is to reduce the shearing effect of the choke. Separators are conventionally designed based on initial flow rates; as a result, the separator is no longer able to accommodate totality of produced fluids. Changing fluid flow rates as well as emulsion viscosity effect separator design. The reduction in vessel performance results in recorded measurements that do not match actual production levels inducing doubt into any history matching process and distorting reservoir management programs. In this paper, the new model takes into account flow rates and emulsion viscosity. The generated vessel length, vessel diameter, and slenderness ratio monographs are used to select appropriate separator size based on required retention time. Model results are compared to API 12J standards.